Targeted Probes for Cardiovascular MR Imaging - Uppal, Ritika (2010)
BACKGROUND: Molecular magnetic resonance (MR) imaging plays an important role in studying molecular and cellular processes associated with heart disease. Targeted probes that recognize important biomarkers of atherosclerosis, apoptosis, necrosis, angiogenesis, thrombosis and inflammation have been developed. DISCUSSION: This review discusses properties of chemically different types of contrast agents including iron oxide nanoparticles, gadolinium based nanoparticles or micelles, discrete peptide conjugates and activatable probes. Numerous examples of contrast agents based on these approaches have been used in preclinical MR imaging of cardiovascular diseases. Clinical applications are still under investigation for some selected agents with highly promising initial results. CONCLUSION: Molecular MR imaging shows great potential for the detection, characterization of a wide range of cardiovascular diseases and for monitoring response to therapy.